Capital and profit sharing in Islamic equity financing : issues and propects - Sadique, Muhammad Abdurrahman (The Other Press, 2012)
This book analyses aspects related to capital and profit sharing in the equity-Hnancing modes employed by Islamic banks. Major topics covered include the signitlcance of existence and presence of capital at the inception of joint equity ventures, possibility of converting debt into capital, formation of equity ventures based on illiquid capital, the method used by Islamic banks for determining the profit sharing ratio in equityfinanced ventures and possible alternatives, and measures and clauses resulting in inhibiting the profit sharing mechanism in the current practice. The first chapter is devoted to an objective assessment of equity financing in the Islamic banking practice today, and to exploring means for enhanced application of equity modes.